Daily Mobility and Social Interactions among Community-Dwelling Older Adults with Pet Dogs in Urban Communities: : A Scoping Review - Costa, Suellen (2022)
Dogs are part of many people’s lives and are involved in interventions to improve the well-being of older adults in institutional settings. However, the literature on the impact of pet dogs on community-dwelling older adults is still relatively limited. This study mapped the impact of having a companion dog on the daily mobility and social interactions of community-dwelling older adults using a scoping review. Electronic databases were searched, and studies written in English, Portuguese, and Spanish that were published in a peer-reviewed journal were identified. After a careful review, 26 eligible studies were identified, and relevant findings were extracted. The main findings indicated that having a dog may promote or hinder daily mobility and social interactions and that having a dog is about routines and sharing affection. More research is needed to clarify what makes having a companion dog key to promoting active and healthy aging.